Analysis of Emergent Strategy Business Network Clinic PT. Amalia Jannah Medika During the Covid-19 Pandemic - Afrini Saraswati; Shirly Kumala; Indah Masri (Institute of Computer Science (IOCS), 2022)
The Covid-19 pandemic has had an unhealthy impact on the economy, in line with this many companies are updating and adjusting their corporate strategies in order to survive or to continue to grow in these circumstances. The purpose of this study was to analyze the internal and external environmental factors of PT. Amalia Jannah Medika so that she can find out alternative strategies that can be used during the Covid-19 Pandemic. This type of research uses an exploratory descriptive method. Collecting data using direct observation, structured interviews and focus group discussions (FGD). The population and research sample are policy makers and PICs in each clinical branch of PT. Amalia Jannah Medika. Analysis of the data on the strength and weakness factors used the Internal Factor Evaluation (IFE) matrix and the External Factor Evaluation (EFE) matrix, then to look for alternative strategies using the Strength, Weakness, Opportunity, Threat (SWOT) matrix and to determine the most appropriate strategy for implemented using the Quantitative Strategic Planning Matrix (QSPM). The results of the SWOT analysis of PT. Amalia Jannah Medika is in quadrant I with aggressive criteria so that the recommended alternative strategy to be implemented is the strength-opportunities strategy. Furthermore, based on the results of the QSPM analysis, the selected strategy was obtained, namely increasing the marketing of PT. Amalia Jannah Medika through digital marketing by joining various health and tourism marketplaces and platforms.